Assessment of water losses in distribution networks: Municipality of Chimoio, Mozambique - Khanlawia, António (2022)
Water is vital for human survival, health and dignity. However, freshwater resources are under increasing pressure due to increasing population growth and increasing economic activities. Water supply systems, due to their complexity and specificity, introduce a certain degree of production loss. Therefore, in Mozambique, there is a great concern of the water distribution company and the researchers in the search for solutions for the implementation of operational processes that minimize water losses. Thus, the research aimed to evaluate water losses in the supply network in the Municipality of Chimoio, Zone 25 de Junho. The study was based on the determination of the water balance, hydraulic modeling and its calibration, using the Epanet 2.0 Software. The results obtained indicate that the rate of water losses in the supply network was 25% and losses significantly influenced the pressure and flow variables.